A real time PCR assay on blood for diagnosis of invasive candidiasis in immunocompromised patient - Mohsen Ashrafi; Mojtaba Nabili; Tahereh Shokohi; Ghasem Janbabaie; Mohamad Taghi Hedayati; Kamran Ali-Moghaddam (Mazandaran University of Medical Sciences, 2015)
Background and Purpose: Invasive candidiasis (IC) is a significant cause of morbidity and mortality in patients with hematologic disorders and bone marrow transplant recipients. Rapid, specific and sensitive test for the timely accuracy in immunocompromised patients to reduce mortality rates and prevent IC progress is necessary. We established a real-time PCR assay on blood for the diagnosis and differentiation of the causative Candida species. Materials and Methods: Whole blood samples were collected twice, from 72 patients for Real Time PCR and blood culture assays. The primers and hybridization probes were designed to potentiate the specific sequence of 18S rRNA genes using Light Cycler system and Fluorescence Resonance Energy Transfer (FERT). The patients with hematologic malignancies and bone marrow transplant recipients were evaluated for IC based on the revised European Organization for Research and Treatment of Cancer/ Mycoses Study Group (EORTC/MSG) criteria. Results: From 2009 to 2011, 72 patients with hematologic malignancies and bone marrow transplant recipients were evaluated for IC. The female to male ratio was 27:45; the mean age was 32.1 years. The most common malignancy in this patient was acute myeloid leukemia (AML) (27.8%) and acute lymphoblastic leukemia (ALL) (26.4%). Out of 72 patients, 11 patients (15.3%) had positive real time PCR /probe results. Based on the melting temperature (Tm) analysis, 5 (45.4%) C. krusei, 3 (27.2%) C. tropicalis, 2 (18.1%) C. parapsilosis and 1 C. albicans (9%) were identified. According to the revised EORTC / MSG, 1 patient (9%) and 10 patients (91%) were defined as proven and possible groups of IC, respectively. The mortality rate in proven and possible IC patient was found 54.5%. Conclusion: The established Real-time PCR/FRET probe assay is an appropriate diagnostic tool for the detection of Candida species DNA and the management of patients suffering from hematologic malignancies and bone marrow recipient are at risk for IC.